Identyfikacja przewagi konkurencyjnej spółki Prokom przy wykorzystaniu wyceny przedsiębiorstwa mnożnikiem cena/zysk - Słoński, Tomasz; Siedlecki, Rafał (The Prokom's competitive advantage measurement using P/E valuation model, 2006)
The P/E valuation model includes value drivers estimations. Positive rate of return spread (the difference between required and realized rate of return) is the measure of competitive advantage. Using normalized P/E ratio as a reference point allows to estimate abnormal rate of returns and competitive advantage period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 473-480